Analysis of The Influence of Brand Image, Digital Marketing and Product Knowledge on Customers Purchase Intention of Banking Products - Febri Sari Siahaan; Irma M. Nawangwulan; Hari Setia Putra; Samuel PD Anantadjaya; Sukma Irdiana (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2023)
The purpose of this study is to determine whether there is a simultaneous relationship between digital marketing, brand image, and product understanding on the decision to become a customer. In this study, the population consists of all Sharia bank customers. With a total of 100 respondents, this study used a non-probability sampling strategy. This study employs a quantitative methodology and a causal research design, gathering information with a questionnaire. The decision to become a customer was found to be significantly influenced in a good way by digital marketing, according to the research findings. This indicates that the decision to become a customer can be influenced by digital marketing. The more effectively digital marketing is implemented, the more it will persuade consumers to become clients. The decision to become a customer is positively and significantly influenced by brand image. This implies that the decision to become a customer may be influenced by brand image. Making the choice to become a customer will be simpler the more positively the brand is portrayed. The decision to become a customer is positively and significantly impacted by product knowledge. This implies that product expertise can affect a potential customer's choice to buy.